Design and fabrication of ice crusher - Ramfauzan, Ramlee (Universiti Malaysia Sarawak, UNIMAS, 2006)
iii ABSTRACT In order to serve fast cold drink, the user just needs to add ice in their drink as a simple alternative rather than using freezer. I ce crusher machine is the way to crush the ice into the small texture . The smaller the ice’s texture the faster it cools the drink. I ce crusher machine can be divided into two major types that are ice block crusher machine and ice cube crusher machine . However, the existin g ice crusher machine still having problem s in term of safety, mechanism of motion, texture of ice produced and the maximum size of ice that it can be hold for producing ice flakes . This project is focus ing on redesign ing and constructing a new block ice crusher machine. Therefore, several of the problems of the existing machine need to be reduced and eliminate. Several parameters are discussed and analysed in order to build the new machine in term of cost, material selection and manufacturing selection.